Safety evaluation of Veillonella atypica FB0054 with genotoxicity and subchronic toxicological studies - Preece, Kayla E.; Glávits, Róbert; Murbach, Timothy S.; Endres, John R.; Hirka, Gábor; Vértesi, Adél; Béres, Erzsébet; Szakonyiné, Ilona Pasics (Journal of applied toxicology, 2023)
Veillonella atypica is a nonmotile, nonsporulating anaerobic bacteria commonly found in various human biofilms. V. atypica FB0054 was isolated from the gastrointestinal tract of marathon runners, who have increased amounts of this species after athletic events. Interestingly, the consumption of this strain by rodents has been shown to increase their treadmill endurance, leading to the hypothesis that consumption of this species may improve athletic performance in humans as well. Further evaluation, in humans, of the usefulness of this strain should be preceded by safety studies. Therefore, the genotoxic and subchronic toxicological potential was evaluated as a contribution to this effort. Genotoxicity investigation was performed using the in vivo comet assay and in vivo mammalian micronucleus assay due to the anaerobic characteristic of the strain. A 90‐day, repeated‐dose oral toxicity study was performed in rats up to 2200 mg/kg bw/d to investigate general toxicity and identify any target organs. Mitsuoka buffer, a solution shown to preserve the viability of anaerobic bacteria, was used as the vehicle. All three studies revealed no toxicological effects from exposure to FB0054 was isolated from the gastrointestinal tract of marathon runners, who have increased amounts of this species after athletic events. Interestingly, the consumption of this strain by rodents has been shown to increase their treadmill endurance, leading to the hypothesis that consumption of this species may improve athletic performance in humans as well. Further evaluation, in humans, of the usefulness of this strain should be preceded by safety studies. Therefore, the genotoxic and subchronic toxicological potential was evaluated as a contribution to this effort. Genotoxicity investigation was performed using the in vivo comet assay and in vivo mammalian micronucleus assay due to the anaerobic characteristic of the strain. A 90‐day, repeated‐dose oral toxicity study was performed in rats up to 2200 mg/kg bw/d to investigate general toxicity and identify any target organs. Mitsuoka buffer, a solution shown to preserve the viability of anaerobic bacteria, was used as the vehicle. All three studies revealed no toxicological effects from exposure to FB0054 at the highest doses tested. Veillonella atypica is an anaerobic bacteria found in human biofilms. A specific strain, V. atypica FB0054, was isolated from the stool of marathon runners. Its investigation as a probiotic should be preceded by a safety evaluation. The in vivo comet assay and in vivo mammalian micronucleus assay revealed a lack of genotoxicity. A no‐observed‐adverse‐effect‐level of 2200 mg/kg bw/d in rats, the highest dose tested, was determined based on the results of a repeated‐dose subchronic oral toxicity study.